Application Solution on Network Video Industry - Guanzhong Lv; Yuandong Ma (Dianxin kexue)
In recent years,research on the online video industry application solutions focused on the video surveillance industry and the hotel industry.These applications only solves part of the application type,there are many more did not meet industry needs.The case IPTV video applications in cooperation with universities,the proposed opening of the IPTV architecture to meet their own content and copyrighted content mixed service industry application mode1,not only provides high-quality copyrighted video content for college teachers and students,but also for the university's own rich video resources,including events,seminars,campus TV station etc.,to provide a platform for publishing channels and services.